Carbohydrate intake and training efficacy - a randomized cross-over study - Beaudouin, F.; Joerg, F.; Hilpert, A.; Meyer, T.; Hecksteden, A. (Journal of Sports Sciences, 2018)
Carbohydrate (CHO) availability during endurance exercise seems to attenuate exercise-induced perturbations of cellular homeostasis and might consequently diminish the stimulus for training adaptation. Therefore, a negative effect of CHO intake on endurance training efficacy seems plausible. This study aimed to test the influence of carbohydrate intake on the efficacy of an endurance training program on previously untrained healthy adults. A randomized cross-over trial (8-week wash-out period) was conducted in 23 men and women with two 8-week training periods (with vs. without intake of 50g glucose before each training bout). Training intervention consisted of 4x45 min running/walking sessions/week at 70% of heart rate reserve. Exhaustive, ramp-shaped exercise tests with gas exchange measurements were conducted before and after each training period. Outcome measures were maximum oxygen uptake (VO2max) and ventilatory anaerobic threshold (VT). VO2max and VT increased after training regardless of CHO intake (VO2max: Non-CHO 2.6 ± 3.0 ml/min*kg p = 0.004; CHO 1.4 ± 2.5 ml/min*kg p = 0.049; VT: Non-CHO 4.2 ± 4.2 ml/min*kg p < 0.001; CHO 3.0 ± 4.2 ml/min*kg p = 0.003). The 95% confidence interval (CI) for the difference between conditions was between +0.1 and +2.1 ml/min*kg for VO2max and between -1.2 and +3.1 for VT. It is concluded that carbohydrate intake could potentially impair the efficacy of an endurance training program.